Sikkim Development Report - Planning Commission (Planning Commission, 2001)
The State Development Report for Sikkim has been prepared with generous contributions of many individuals and organizations. The Planning Commission, Government of India, entrusted the task of preparing the Report to National Institute of Public Finance and Policy (NIPFP), New Delhi. Professor Mahendra Lama, Vice Chancellor, Central University of Sikkim, Gangtok (formerly, Professor, School of International Studies, JNU, New Delhi), was taken as a collaborating partner. We are grateful to all authors, experts and peer reviewers for their timely contributions.
Planning Commission Government of India
Planning Commission Government of India